Balancing the Tide of Globalization: Maintaining Afro-Caribbean Cultural Power and Indigenous Identity in the Dance Studio. (2014) - Wilson, Lisa
Abstract : Historically, during the first wave of globalization, then known as colonialism, efforts were made by colonizers to silence indigenous cultural expressions as a means of establishing power and control. In this current wave of globalization, which is marked by an aggressive technological revolution that has facilitated greater connectedness and spread of the more dominant North Atlantic aesthetic values and practices across the globe, Afro-Caribbean traditional cultural expressions face the potential risk of being obsolete and powerless in the dancing lives of young studio-based dancers in the Caribbean. This paper presents findings of a qualitative study into measures taken by Caribbean dance teachers (n = 6), from Jamaica, Grenada, and St. Vincent and the Grenadines, to promote Afro-Caribbean movement aesthetics and practices in their dance studios with young people. I will argue that such measures are important to the empowerment of the Afro-Caribbean dancing body and to safeguard against colonial structures in post-colonial Caribbean dance education.